2005
DOI: 10.1111/j.0303-6987.2005.00301.x
|View full text |Cite
|
Sign up to set email alerts
|

Basal cell carcinoma with matrical differentiation: a case study with analysis of β‐catenin*

Abstract: Matrical differentiation in basal cell carcinoma (BCC) is rare. Only nine cases have been described that showed typical diagnostic features of BCC, in addition to shadow cells indicating hair-matrix differentiation. These cases often present a diagnostic challenge due to confusion with pilomatrixoma or pilomatrix carcinoma. We present a case of BCC with matrical differentiation in a 78-year-old man. Immunohistochemical and molecular methods are used to differentiate this lesion from benign or malignant forms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 22 publications
0
30
0
Order By: Relevance
“…After the dissection of these 2 distinct parts of that tumor, genetic analysis showed that the mutation is confined to the cystic pilomatricoma-like area. In the 2 remaining cases of BCC with shadow cells, both of them morphologically displaying minor scattered foci of matrical differentiation, exon 3 of the gene retained a wild-type sequence like in the case reported by Haskell et al 22 In the skin, S37F mutation has been reported in squamous cell carcinoma with matrical differentiation and pilomatrical carcinoma. 13,14 Of the 15 trichoblastomas included in the study, only in 1 case was a CTNNB1 mutation found (C23N).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…After the dissection of these 2 distinct parts of that tumor, genetic analysis showed that the mutation is confined to the cystic pilomatricoma-like area. In the 2 remaining cases of BCC with shadow cells, both of them morphologically displaying minor scattered foci of matrical differentiation, exon 3 of the gene retained a wild-type sequence like in the case reported by Haskell et al 22 In the skin, S37F mutation has been reported in squamous cell carcinoma with matrical differentiation and pilomatrical carcinoma. 13,14 Of the 15 trichoblastomas included in the study, only in 1 case was a CTNNB1 mutation found (C23N).…”
Section: Discussionmentioning
confidence: 57%
“…22 This is probably true and one should also consider that a pilomatricoma, as it goes through various stages in its development, contained fewer viable cells toward the end of its ''life.'' On the other hand, we, among others, were able to detect mutation in tumors with minimal areas of supramatrical/matrical cells.…”
Section: Discussionmentioning
confidence: 99%
“…[44][45][46][47] The shadow cells have an anucleate morphology and eosinophilic cytoplasms often accompanied by zones of calcification. 45 Mitoses, apoptic cells and high-grade nuclear atypia are absent.…”
Section: Follicular Bccmentioning
confidence: 99%
“…These include, but are not restricted, to keratotic BCC, 39 infundibulocystic BCC (Figure 12), 42,43 follicular BCC, [44][45][46][47] which shows collision features with pilomatricoma, pleomorphic BCC ( Figure 13), 48,49 BCC with eccrine differentiation, [50][51][52] BCC with sebaceous differentiation, the fibroepithelioma of Pinkus (Figure 14), 53 and the BCC with myoepithelial differentiation. 54 Keratotic BCC Also known as pilar BCC as it appears to differentiate along pilosebaceous lines, the keratotic BCC manifests large basaloid tumor nests that are rounded and show central keratinization and degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, one of the most important differential diagnoses to be ruled out is basal cell carcinomas with matrical differentiation, which presents as a slowly growing ulcerated nodule, commonly in elderly men. Histopathological features of basal cell carcinoma with matrical differentiation include infiltrative tumour aggregates, peripheral nuclear palisading, and retraction clefts [12,[41][42][43][44][45][46][47] . Moreover, basal cell carcinomas with matrical differentiation shows positivity towards Ber-EP4 [1,2,34] and a focal and membranous pattern [44,46] of staining with beta-catenin, in contrast to melanocytic matricomas, which is negative to Ber-EP4 [4,7,11] and show an intense, pattern of nuclear and cytoplasmic positivity to beta-catenin [9,11,18] .…”
Section: Melanocytic Matricomamentioning
confidence: 99%